The ludic-aesthetic-poetic universe in music education: a philosophical approach - Cardoso, Renato [UNESP]; MUSICOGUIA (Musicoguia, 2021)
In investigating the formation of knowledge and human identity, Edgar Morin, thinker of complexity, underscored that there is much more to human understanding than just rationality. Incorporating Morin ' s contributions to music education philosophy, in this paper, I discuss the concept of ludic-aesthetic-poetic universe and its capability to contemplate and surpass the role of rationality in musical knowledge. To this end, I adopt the philosophical method of synopsis, which consists of constructing one's own perspective deliberately viewing together of aspects of human experience. The ludic is an element of culture, described as significant form, as social function, transcending immediate life needs in which individuals fully commit to an activity that belongs to a specific dimension of life. The aesthetic is related to sensuous experience and its power to subjective transformation. As an end in itself, it is not exclusively related to arts. There is an aesthethic dimension of being. The poetic is the manifestation of living poetry, the utmost state of meaning-making. Taken together, the ludic, aesthetic and poetic dimensions of experience expand the archaic notion of knowledge equals reason, opening a window of opportunity to consider the arts generally and music specifically as an important component for the construction of knowledge in educational contexts.
Keywords: Music Education; Philosophy; Aesthetic; Musical knowledge; Complexity